Universalidade e regionalismo na obra de José Siqueira: construção das edições crítica e de performance da II sonata para violoncelo e piano - Silva, Marcelo Moreno da (2023)
This research presents an analysis focused on performance, based on references of Brazilian cultural expressions from the Northeast of Brazil present in the II Sonata for Cello and Piano by the composer José Siqueira, from Paraíba. At the same time that we propose the elaboration of a Critical Edition as well as Performance Edition of the Sonata, we use notions from the Trimodal System (SIQUEIRA, 1981a) developed by the composer himself. Thus, we found tools to identify patterns that helped to propose solutions for eventual inconsistencies in the handwritten copies, the main primary documental sources for this work. We point out that these primary sources concern the composer's manuscript as well as fair copy prepared by F. Paes de Oliveira. Together, they proved to be indispensable tools to the work’s compositional understanding. As a way of proposing interpretative possibilities for the Sonata, we held a discussion about concepts about Timing applied in the performance of the work based on the study of Matthay (1913), Cone (1968), Epstein (1995), Aquino and Aquino (2021). In order to investigate Siqueira's cellistic and regionalist language, juxtaposed with his compositional universality, the research seeks to identify possible influences absorbed by Siqueira through the artists with whom he lived and were related to. It is in this context that we identify supposed traits of the British composer Benjamin Britten in the elaboration of this work. In this way, parallel to the composer-performer relationship between Britten and the Russian cellist Mstislav Rostropovich, Siqueira also dedicated this Sonata to the cellist. By investigating a Brittenian language and/or aspects in the Sonata, this study also intends to understand Rostropovich's influence on the 20th century cello repertoire to investigate whether the ties between Siqueira and Rostropovich are only in the dedication of the score or in the composition itself